1989
DOI: 10.1111/j.1365-277x.1989.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Infant feeding fractices within white and Asian Communities in inner‐city Leeds

Abstract: A structured questionnaire was devised in order to ascertain infant feeding practices. Multi‐lingual interviewers visited the homes of 127 Caucasian and 184 Asian families with infants aged 6–24 months, in inner‐city Leeds. The Asian families interviewed were from four‐defined communities; Bangladeshis, Pakistanis, Punjabis and Gujaratis. When compared with asian mothers, Caucasian mothers were more likely to breast‐feed, and demonstrated a more positive approach to their chosen feeding pattern whether breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Compared with white mothers, Asian mothers tend to introduce solid foods later,7 8 14 15 and although we confirmed this finding,4 more than 90% of children from all groups were receiving some solids by 4 months of age. Asian children are reported to receive more sweet desserts and fewer savoury and meat based foods than white children during infancy,7 15 although Thomas and Avery showed that only Bangladeshi children ate desserts more frequently than white children 4.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…Compared with white mothers, Asian mothers tend to introduce solid foods later,7 8 14 15 and although we confirmed this finding,4 more than 90% of children from all groups were receiving some solids by 4 months of age. Asian children are reported to receive more sweet desserts and fewer savoury and meat based foods than white children during infancy,7 15 although Thomas and Avery showed that only Bangladeshi children ate desserts more frequently than white children 4.…”
Section: Discussionmentioning
confidence: 39%
“…The use of feeding bottles after the age of 1 was associated with higher milk consumption,4 and previous studies have described prolonged use of feeding bottles in Asian children 714 15 We found that at 15 months at least 90% of Asian children were still bottle fed, if only partially, compared with 75% of white children; 67% of white children drank milk from a cup at this age compared with 50% of Indian, 41% of Pakistani, and 26% of Bangladeshi children 4. The addition of cereal or sugar is more common among Asian mothers14; in the current survey approximately a third of Bangladeshi mothers added something to the milk of their 15 month old child: mainly rusk, baby rice, or other cereal; 10% of Pakistani mothers added sugar.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast, parents in district N may prefer to delay their baby's progression onto a feeder cup and be less aware of the cariogenic effects of many baby drinks. It has been shown that Asian parents are more likely to keep their children on bottles of milk sweetened with sugar, rusks or honey 16 for years and this could be why the level of nursing caries is higher among Asian children in district C. Local social support for healthy or more harmful child-rearing practices is likely to be an important influence on the prevalence of nursing and general caries.…”
Section: Discussionmentioning
confidence: 99%
“…It studied cross-sectionally a representative sample of British infants aged between 6 and 12 months (Mills & Tyler, 1992). Other smaller studies have focused on the Asian community in Britain (Harbottle & Duggan, 1994), and differences between the Asian community and other ethnic groups (Warrington & Storey, 1988;Williams et al, 1989).…”
Section: Introductionmentioning
confidence: 99%